Effect of compost enrichment with Trichoderma sp on the growth of Arabica coffee seedlings. Issue 1 (October 2020) - Ala, A; Musa, Y; Kadola, L
Abstract: An experiment was conducted to determine and study the effect of adding Trichoderma sp. on compost for the growth of Arabica coffee seedlings ( Coffea arabica L.). The research design was a complete randomized design (CRD) of a two-factor factorial pattern. Compost was the first factor consisted of 4 levels: 0 g per polybag, 100 g per polybag, 200 g per polybag, 300 g per polybag, and Trichoderma sp addition as the second factor consisting of 4 levels, namely: 0 g per polybag, 1 g per polybag, 2 g per polybag, 3 g per polybag. The results showed that the compost dosage of 300 g / polybag gave the best results on average leaf area parameters (22.22 cm), stem diameter (3.27 mm), and the highest percentage of succesful shoot grafting which was 86.11%. Addition of 2 g Trichoderma sp. per polybag gave the best results on leaf area at the age of 6 week after planting of 6.38 cm.